2015
DOI: 10.1371/journal.pone.0130847
|View full text |Cite|
|
Sign up to set email alerts
|

Latitudinal Gradient in Otolith Shape among Local Populations of Atlantic Herring (Clupea harengus L.) in Norway

Abstract: Otolith shape analysis of Atlantic herring (Clupea harengus) in Norwegian waters shows significant differentiation among fjords and a latitudinal gradient along the coast where neighbouring populations are more similar to each other than to those sampled at larger distances. The otolith shape was obtained using quantitative shape analysis, the outlines were transformed with Wavelet and analysed with multivariate methods. The observed morphological differences are likely to reflect environmental differences but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…Regardless of whether deacon rockfish were organized into nearshore and offshore groups, morphological and genetic differences were statistically significant but small among the sample sites. Although our morphometric and genetic results were comparable to findings from other marine fishes sampled over larger geographic distances (Benestan et al, ; Berg et al, ; Lee et al, ; Libungan et al, ; Soeth et al, ), previous stock assessment using similar methods has relied upon stronger patterns in data to delineate a stock boundary (Siegle, Taylor, Miller, Withler, & Yamanaka, ; Ward, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Regardless of whether deacon rockfish were organized into nearshore and offshore groups, morphological and genetic differences were statistically significant but small among the sample sites. Although our morphometric and genetic results were comparable to findings from other marine fishes sampled over larger geographic distances (Benestan et al, ; Berg et al, ; Lee et al, ; Libungan et al, ; Soeth et al, ), previous stock assessment using similar methods has relied upon stronger patterns in data to delineate a stock boundary (Siegle, Taylor, Miller, Withler, & Yamanaka, ; Ward, ).…”
Section: Discussionsupporting
confidence: 81%
“…Estimated pseudo F-values for the PERMANOVA test (Table 3) were similar to results reported in previous shaper otolith shape analyses of fish populations sampled over larger geographic distances (Berg et al, 2018;Lee, Brewin, Brickle, & Randhawa, 2018;Libungan, Slotte, Husebø, Godiksen, & Pálsson, 2015;Soeth et al, 2018). Additionally, a similar pattern of otolith shape variation was reported for two rockfish species sampled across the North Atlantic Ocean (Stransky, 2005).…”
Section: Concordance Between Otolith Shape and Genetic Variationsupporting
confidence: 84%
“…Similar results have been observed in Nordfjord, although these are not as clear as in Sognefjorden. Libungan et al [ 56 ] demonstrated differences in otolith shape for herring from these fjords, supporting our notion of local populations. According to VS, Nordfjord is also a nursery area for NSS.…”
Section: Discussionsupporting
confidence: 89%
“…Iles and Sinclair [ 6 ] proposed that Atlantic herring have complex population structure and much effort has been spent to resolve this structure. Phenotypic traits like growth [ 7 , 8 ], numbers of vertebrae [ 9 , 10 ], otolith microstructure [ 11 , 12 ], as well as otolith shape [ 13 15 ], have been used to investigate the population structure of herring. Genetic studies have also become important during recent years.…”
Section: Introductionmentioning
confidence: 99%